2014
DOI: 10.1080/09593330.2014.952344
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular polymeric substances production kinetics of 13 sludge isolates using wastewater sludge as raw material and its flocculation potential

Abstract: The kinetics of batch fermentation of 13 extracellular polymeric substances (EPS) producing bacterial strains (9 Bacillus, 2 Serratia and 2 Yersinia) were carried out using sterilized sludge as a raw material. The most of Bacillus (µ(max): 0.11-0.27 h⁻¹), Serratia (µ(max): 0.23-0.27 h⁻¹) and Yersinia (µ(max): 0.18-0.19 h⁻¹) strains had capability to grow and produce EPS (1.36-2.12 g/L) in the sterilized sludge. In general, EPS production was mixed growth associated for all the bacterial strains cultivated inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(67 reference statements)
2
4
0
Order By: Relevance
“…A decrease in B-EPS concentration (from 13.3 to 11.4 g/L) was observed between 48 and 96 h. This decrease could be due to the fact that the bacteria may have consumed EPS when carbon limitation occurred in the medium. This phenomenon was also observed by other researchers using pure or mixed culture in sludge or synthetic medium [2,16]. According to More et.…”
Section: Sludge Dewaterabilitysupporting
confidence: 48%
See 3 more Smart Citations
“…A decrease in B-EPS concentration (from 13.3 to 11.4 g/L) was observed between 48 and 96 h. This decrease could be due to the fact that the bacteria may have consumed EPS when carbon limitation occurred in the medium. This phenomenon was also observed by other researchers using pure or mixed culture in sludge or synthetic medium [2,16]. According to More et.…”
Section: Sludge Dewaterabilitysupporting
confidence: 48%
“…al. [2] investigated the effect of fermentation time on EPS production in activated sludge and found that the EPS content was proportional to the bacterial growth. A decrease in B-EPS concentration (from 13.3 to 11.4 g/L) was observed between 48 and 96 h. This decrease could be due to the fact that the bacteria may have consumed EPS when carbon limitation occurred in the medium.…”
Section: Sludge Dewaterabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The sludge media was prepared using different sludge solid concentrations (5,10,20,30 The crude glycerol used in this experiment was obtained from Bio-Liq, Quebec, Canada. The crude glycerol contained 675 g/L of glycerol.…”
Section: Media Preparationmentioning
confidence: 99%